Lithium silicate nanosheets with excellent capture capacity and kinetics with unprecedented stability for high-temperature CO2 capture - Belgamwar, Rajesh; Maity, Ayan; Das, Tisita; Chakraborty, Sudip; Vinod, Chathakudath P.; Polshettiwar, Vivek (Chemical Science, 2021)
An excessive amount of CO2 is the leading cause of climate change, and hence, its reduction in the Earth's atmosphere is critical to stop further degradation of the environment. Although a large body of work has been carried out for post-combustion low-temperature CO2 capture, there are very few high temperature pre-combustion CO2 capture processes. Lithium silicate (Li4SiO4), one of the best known high-temperature CO2 capture sorbents, has two main challenges, moderate capture kinetics and poor sorbent stability. In this work, we have designed and synthesized lithium silicate nanosheets (LSNs), which showed high CO2 capture capacity (35.3 wt% CO2 capture using 60% CO2 feed gas, close to the theoretical value) with ultra-fast kinetics and enhanced stability at 650 degrees C. Due to the nanosheet morphology of the LSNs, they provided a good external surface for CO2 adsorption at every Li-site, yielding excellent CO2 capture capacity. The nanosheet morphology of the LSNs allowed efficient CO2 diffusion to ensure reaction with the entire sheet as well as providing extremely fast CO2 capture kinetics (0.22 g g(-1) min(-1)). Conventional lithium silicates are known to rapidly lose their capture capacity and kinetics within the first few cycles due to thick carbonate shell formation and also due to the sintering of sorbent particles; however, the LSNs were stable for at least 200 cycles without any loss in their capture capacity or kinetics. The LSNs neither formed a carbonate shell nor underwent sintering, allowing efficient adsorption-desorption cycling. We also proposed a new mechanism, a mixed-phase model, to explain the unique CO2 capture behavior of the LSNs, using detailed (i) kinetics experiments for both adsorption and desorption steps, (ii) in situ diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy measurements, (iii) depth-profiling X-ray photoelectron spectroscopy (XPS) of the sorbent after CO2 capture and (iv) theoretical investigation through systematic electronic structure calculations within the framework of density functional theory (DFT) formalism.

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions

Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides

Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis